Dear friends, Please read our latest blog post for an important announcement about the website. ❤, The Socratic Team

If, y = (√x)+(1/√x) so prove that ? 2x(dy/dx)+y = 2√x

2 Answers
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

2
Jun 17, 2018

Answer:

#y+2x(dy/dx)= 2sqrt(x)#

Explanation:

#y = sqrt(x) + 1 /sqrt(x)#

#sqrt(x).y = x +1#

#(1/(2*sqrt(x))).y+sqrt(x).dy/dx = 1#

#y=2.sqrt(x)(1-sqrt(x).dy/dx)#

#y=2.sqrt(x) - 2x .dy/dx#

#y + 2x .(dy/dx) = 2.sqrt(x)#

Was this helpful? Let the contributor know!
1500
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Jun 19, 2018

Answer:

Please see a Proof in the Explanation.

Explanation:

Given that, #y=sqrtx+1/sqrtx=x^(1/2)+x^(-1/2)#.

Recall that, #d/dx(x^n)=n*x^(n-1)#.

#:. dy/dx=1/2*x^(1/2-1)+(-1/2)*x^(-1/2-1)#.

# =1/2*x^(-1/2)-1/2*x^(-3/2)#,

#:. dy/dx=1/2{x^(-1/2)-x^(-3/2)}#.

Multiplying this eqn. by #2x#, we get,

#2xdy/dx=cancel(2)x*1/cancel(2){x^(-1/2)-x^(-3/2)}#,

#=x*x^(-1/2)-x*x^(-3/2)#,

# i.e., 2xdy/dx=x^(1/2)-x^(-1/2)=sqrtx-1/sqrtx#.

Finally, adding #y=sqrtx+1/sqrtx#, we have,

#2xdy/dx+y=(sqrtxcancel(-1/sqrtx))+(sqrtxcancel(+1/sqrtx))#,

# or, 2xdy/dx+y=2sqrtx#,

as Respected Abhishek Malviya has readily derived!

Was this helpful? Let the contributor know!
1500
Trending questions
Impact of this question
41 views around the world
You can reuse this answer
Creative Commons License